2017
DOI: 10.1136/jech-2016-207691
|View full text |Cite
|
Sign up to set email alerts
|

levels and sociodemographic correlates of accelerometer-based physical activity in Irish children: a cross-sectional study

Abstract: PA levels differed by individual factors including age, gender and weight status as well as by environmental factors including residence and daylight length. Less than one-quarter of children (26.8% boys, 16.2% girls) meet guidelines. Effective intervention policies are urgently needed to increase PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…The US National Health and Nutrition Examination Survey (NHANES) used the ActiGraph wrist-worn accelerometer in cycles 2011-2012 and 2013-2014 (approximately 9,000-10,000 participants examined per cycle). The Pelotas Birth Cohort (6), the Melbourne Child Health Checkpoint (7), the Cork Children's Lifestyle Study (8), and the British Whitehall II study (9) used the GENEActiv in approximately 10,000, 4,000, 1,000 and 3,750 participants, respectively. Before outcomes from studies using different brands of accelerometer can be pooled into multinational databases, it is necessary to demonstrate comparability of data outputs between brands.…”
Section: Introductionmentioning
confidence: 99%
“…The US National Health and Nutrition Examination Survey (NHANES) used the ActiGraph wrist-worn accelerometer in cycles 2011-2012 and 2013-2014 (approximately 9,000-10,000 participants examined per cycle). The Pelotas Birth Cohort (6), the Melbourne Child Health Checkpoint (7), the Cork Children's Lifestyle Study (8), and the British Whitehall II study (9) used the GENEActiv in approximately 10,000, 4,000, 1,000 and 3,750 participants, respectively. Before outcomes from studies using different brands of accelerometer can be pooled into multinational databases, it is necessary to demonstrate comparability of data outputs between brands.…”
Section: Introductionmentioning
confidence: 99%
“…This framework showed that many factors can influence the level of adolescent PA 8. These factors can be classified into three categories7: (1) individual intrinsic motivation9 10; (2) family factors, such as socioeconomic level or parental encouragement and engagement11–13; and (3) general environmental factors, such as an urban environment (eg, access to green public parks, traffic density),14–16 societal environment (eg, school schedule)17 and natural conditions (eg, seasons/meteorological conditions/day length) 18 19. Some previous studies showed that global climate change can alter children’s health and PA pattern 20 21.…”
Section: Introductionmentioning
confidence: 99%
“…Results, however, have been inconsistent. Some studies have shown higher PA and physical fitness levels in urban youth [27][28][29], while others have shown opposite results [2,30,31]. There is also research indicating limited differences in physical fitness by living environment [6,32,33].…”
mentioning
confidence: 99%